A liminal iconotext. Iconological analysis of graffiti signature - González de Requena Farré, Juan A. (2017)
This article aims to make a iconological exegesis of graffiti signature, based on the proposal of Panofsky: we explore its motifs, and some traditions that sustain its ways of meaning will be rebuilt, concluding with an interpretation of the epochal background and cultural understanding that give sense to it. This paper argues that graffiti signature is a type of icononimia or idio-graphy without a script, in which image and text become so inseparable, as undecidable is the meaning of such inscriptionn, ranging from agonist self-expression  to symbolic deregulation associated with banal globalism